Nothing ever happens = Nunca pasa nada - McKinnon, Heidi (Scholastic Inc., 2025)
Two bored little fish long for adventure...but will they get more than they bargained for? Nothing ever happens to two friendly little fish. Same old ocean. Same old seaweed. But when adventure finds them, will these two friends rise to the occasion? Or will they flounder? A fabulously funny picture book about perspective, positive thinking, and unexpected suprises! The perfect read-aloud picture book from award-winning Australian creator Heidi McKinnon. For fans of Finding Dory, The Pout Pout Fish, and Baby Shark!